2005
DOI: 10.1037/1528-3542.5.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Foes and Friends: Perceptual and Emotional Factors When Finding a Face in the Crowd.

Abstract: In a face-in-the-crowd setting, the authors examined visual search for photographically reproduced happy, angry, and fearful target faces among neutral distractor faces in 3 separate experiments. Contrary to the hypothesis, happy targets were consistently detected more quickly and accurately than angry and fearful targets, as were directed compared with averted targets. There was no consistent effect of social anxiety. A facial emotion recognition experiment suggested that the happy search advantage could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
267
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(316 citation statements)
references
References 55 publications
40
267
2
1
Order By: Relevance
“…For instance, participants take longer to count the number of facial features in displays of negative than of positive schematic faces (Eastwood, Smilek, & Merikle, 2003), to respond to the gender of negative than of positive faces (Purcell, Stewart, & Skov, 1998), or to respond to the color of a negative than of a positive face (White, 1996). The findings are also broadly consistent with a number of studies that have found people to be faster and more accurate at identifying happy faces than negative (fearful, angry, sad, or disgusted) faces (Juth et al, 2005;Kirita & Endo, 1995;Leppänen & Hietanen, 2004;Palermo & Coltheart, 2004). For instance, concluded that happy faces were identified more rapidly and required less effort to encode than negative faces.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, participants take longer to count the number of facial features in displays of negative than of positive schematic faces (Eastwood, Smilek, & Merikle, 2003), to respond to the gender of negative than of positive faces (Purcell, Stewart, & Skov, 1998), or to respond to the color of a negative than of a positive face (White, 1996). The findings are also broadly consistent with a number of studies that have found people to be faster and more accurate at identifying happy faces than negative (fearful, angry, sad, or disgusted) faces (Juth et al, 2005;Kirita & Endo, 1995;Leppänen & Hietanen, 2004;Palermo & Coltheart, 2004). For instance, concluded that happy faces were identified more rapidly and required less effort to encode than negative faces.…”
Section: Discussionsupporting
confidence: 89%
“…To do so, we had to avoid the most negative images from the IAPS since they tend to be more highly arousing than the positive images. We also attempted to avoid pictures displaying close-ups of people's faces since there is evidence for a processing advantage for happy faces (Amir, Elias, Klumpp, & Przeworski, 2003;Juth, Lundqvist, Karlsson, & Öhman, 2005;Kirita & Endo, 1995;Leppänen & Hietanen, 2004). Within these constraints, we wanted to maximize the valence difference between our stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…snakes and spiders) is enhanced in individuals reporting high levels of fear or phobia for specific stimuli (Flykt & Caldara, 2006;Öhman, Flykt, & Esteves, 2001;Rinck et al, 2005;Soares, Esteves, Lundqvist, & Öhman, 2009). There is also evidence to suggest that social anxiety and trait anxiety are associated with greater speed and accuracy in searching for and detecting the presence of angry target faces (Gilboa-Schechtman, Foa, & A C C E P T E D M A N U S C R I P T Running Head: ANXIETY, SELECTIVE ATTENTION AND HYPERVIGILANCE Amir, 1999;Byrne & Eysenck, 1995;Juth, Lundqvist, Karlsson, & Öhman, 2005). Further studies have varied set size in order to assess the effect of anxiety on search efficiency as indexed by the gradient and intercept of the search slope (Eastwood et al, 2005;Matsumoto, 2010).…”
Section: Empirical Evidence For Superior Threat Detection In Anxietymentioning
confidence: 99%
“…perceptual comparisons across faces (Frischen, Eastwood & Smilek, 2008;Horstman, 2009;Juth et al, 2005). For example, the happy face advantage seems to involve an interplay between emotional and perceptual factors.…”
Section: Visual Search For Emotional Expressions In Autismmentioning
confidence: 99%